(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Women in indigenous societies now understand the value of a formal education. They want tofurther their education, find gainful job, maintain a comfortable standard of living, and enhance theiroverall quality of life. The educational infrastructure in indigenous communities is underdeveloped. Manygaps exist in the current educational system. Improvements in these areas need the development ofappropriate policies and procedures. There are several obstacles that the indigenous women face as theytry to further their education. One of the main issues is that they do not always get help and supportfrom their loved ones. The indigenous people also live in situations of poverty and social backwardness.This means that many challenges must be overcome by indigenous women before they may improvetheir standard of life via education. Yet, attitudes among tribal people are shifting, and more and moreparents are pushing their daughters to get an education. Hence, it is important to motivate indigenouswomen to further their education, and changes should be made to the educational system as a whole.This study focuses on the challenges faced by tribal women in their pursuit of higher education, as wellas the solutions that have been proposed to address these issues.